Prototyping of Agricultural Education Website Using the Design Sprint Approach - Hadiq Hadiq; Eko Heri Susanto; Rina Permata Sari (Universitas Raharja, 2021)
Agricultural technology is developing in line with discoveries in soil science and plant nutrition. This technology enables increased tonnage of yields at lower costs. But unfortunately, this useful technological development cannot be directly applied by farmers due to the slow transformation of information to farmers. One thing that can be done is to create an appropriate agricultural technology information service website. For the information presented to suit the farmers' needs and easy for them to understand, a user interface design process is needed that involves the farmer directly. So this study uses Design Sprint as an approach to design and validate the user interface. This research succeeded in making a website template design and has been validated with a grade of 3.6 from a scale of 5. The grade is included in the category of very good and suitable for use as an educational medium.